What determines firms' decisions to formalize? Evidence from rural Indonesia - Neil McCulloch; Günther G. Schulze; Janina Voss (University of Freiburg, Department of International Economic Policy (iep), 2010)
In this paper we analyze the decision of small and micro firms to formalize, i.e. to obtain business and other licenses in rural Indonesia. We use the rural investment climate survey (RICS) that consists of non-farm rural enterprises, most of them microenterprises, and analyze the effect of formalization on tax payments, corruption, access to credit and revenue, taking into account the endogeneity of the formalization decision to such benefits and costs. We show, contrary to most of the literature, that formalization reduces tax and corruption payments. The benefits of formalization, and therefore the likelihood of being formal, also depend on characteristics such as firm size, as well as the education and ethnicity of the owner.
Keywords: O17; O18; 330; formalization; rural development; rural investment climate; informal sector